2018
DOI: 10.4193/rhin17.253
|View full text |Cite
|
Sign up to set email alerts
|

mySinusitisCoach: patient empowerment in chronic rhinosinusitis using mobile technology

Abstract: Mobile health technology is emerging to take a prominent position in the management of chronic diseases. These technologies aim at enhancing patient empowerment via education and self-management. To date, of all the different apps available for patients with sinus disease, none were developed by medical experts dealing with chronic rhinosinusitis (CRS). The European Forum for Research and Education in Allergy and Airway diseases (EUFOREA) has undertaken a multi-stakeholder approach for designing, developing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 6 publications
2
48
0
Order By: Relevance
“…It is characterized by inflammation of the nasal mucosa and paranasal sinuses, and by definition, patients with CRS must report the presence of anterior or posterior rhinorrhea, nasal congestion, hyposmia, and/or facial pressure or pain that lasts for more than 12 weeks. 1,2 Although CRS is not life-threatening, symptoms such as nasal congestion, nasal discharge, pain or facial pressure, loss of smell, and cough impair the patient's quality of life and economic activity. 3,4 CRS is heterogeneous and is generally classified into 2 phenotypes, namely, CRS with nasal polyps (CRSwNP) and CRS without nasal polyps.…”
mentioning
confidence: 99%
“…It is characterized by inflammation of the nasal mucosa and paranasal sinuses, and by definition, patients with CRS must report the presence of anterior or posterior rhinorrhea, nasal congestion, hyposmia, and/or facial pressure or pain that lasts for more than 12 weeks. 1,2 Although CRS is not life-threatening, symptoms such as nasal congestion, nasal discharge, pain or facial pressure, loss of smell, and cough impair the patient's quality of life and economic activity. 3,4 CRS is heterogeneous and is generally classified into 2 phenotypes, namely, CRS with nasal polyps (CRSwNP) and CRS without nasal polyps.…”
mentioning
confidence: 99%
“…Prediction of treatment success (43,44) and deciding about the best moment to start a certain treatment (43,44) , prevention of disease (45)(46)(47) and patient participation in the elaboration of the treatment plan (48) is expected to substantially improve the therapeutic approach for individuals suffering from chronic disabling conditions. In this issue of the journal, we report on the use of mySinusitisCoach, an excellent way to involve patients with chronic rhinosinusitis in the management of their disease using mobile technology (48) . The use of mySinusitisCoach facilitates evaluation of patient reported outcome measures and allows not only tailoring of treatment to the level of control of the disease but will also allow us in future to collect longitudinal data about our patient care.…”
Section: Delivering Better Results For Patients Through Core Outcomesmentioning
confidence: 99%
“…Hughes et al provide a brief synopsis of user-generated, ENT-specific educational channels on the popular website YouTube (Google, Mountain View, CA) [39]. A recent review of mobile application stores found 75 mobile apps (as of September 2014) related to resident, student and patient education within otolaryngology, head and neck surgery [40,41]. Among these, apps like "ENT for Students", "ENT Surgery Handbook" and "LearnENT" were highly rated among users and available on multiple platforms [42].…”
Section: The Role Of E-learning In Simulation Trainingmentioning
confidence: 99%